2006
DOI: 10.3122/jabfm.19.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis: A Primary Care Perspective

Abstract: As the population of chronic kidney disease (CKD) and end-stage renal disease (ESRD) grows at an alarming rate, primary care physicians will increasingly be involved in the management of these patients. Early recognition of CKD and timely referral to a nephrologist when glomerular filtration rate approaches 30 mL/min/1.73 m 2 is extremely important to improve ESRD outcome and appropriate selection of dialysis modality. Peritoneal dialysis (PD) remains a viable treatment option for ESRD patients. PD is less exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(37 reference statements)
0
6
0
1
Order By: Relevance
“…That percentage was proportionally higher than the NorthAmerican (8.8%)16 and national (10.6%) 17 means, similar to the mean in Holland (30%) 18 , and lower than the 74% reported in Mexico, the major user of PD worldwide. 7 This reflects our police of impartially presenting the available therapies, allowing patients and their families to freely choose in situations with no contraindication to any method.…”
Section: Discussionmentioning
confidence: 45%
“…That percentage was proportionally higher than the NorthAmerican (8.8%)16 and national (10.6%) 17 means, similar to the mean in Holland (30%) 18 , and lower than the 74% reported in Mexico, the major user of PD worldwide. 7 This reflects our police of impartially presenting the available therapies, allowing patients and their families to freely choose in situations with no contraindication to any method.…”
Section: Discussionmentioning
confidence: 45%
“…HD tedavisinde olduğu gibi makine gereksinimi olmaması, tedavinin doğası gereği sürekli tedavi imkanı sağlaması ve kalan böbrek fonksiyonlarını HD'ye göre daha uzun süre ile koruma imkanı vermesi nedeniyle PD tedavisi bazı avantajlara sahiptir. 3,4 PD tedavisinin bu avantajlarına karşın teknik yetersizlik, tekrarlayan peritonitler, ultrafiltrasyon ve diyaliz yetersizliği, hastanın kendi isteği ve KBH' da ideal tedavi olan böbrek nakli yapılması gibi nedenlerle tedaviden ayrılma görülebilmektedir. KBH' da kardiyovasküler sebeplerden sonra enfeksiyon nedenli ölümler ikinci sırada gelmektedir.…”
Section: Introductionunclassified
“…5 At stage V or end-stage renal disease (ESRD), patients have options for choosing one of the renal replacement therapies (RRTs) in the form of kidney transplantation, hemodialysis (HD), and peritoneal dialysis (PD) either with automated peritoneal dialysis or continuous ambulatory peritoneal dialysis (CAPD). 6,7 In Indonesia, data from nationwide household survey on basic health research showed that the prevalence of CKD increased from 0.2% in 2013 to 0.38% in 2018. 8,9 The major cause of CKD was hypertension, followed by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…CAPD therapy provides better quality of life than HD, allows for flexibility on schedules in conducting self-dialysis, there is less restriction on diet as well as fluid intake, guarantees better preservation of residual renal function, and is less expensive than HD. 2,6,14 A study by Novelia et al indicated that in terms of cost, the average total cost of HD in Indonesia was around IDR 133.4 million or about US$10,000 per patient per year, meanwhile CAPD modality was around IDR 81.7 million or about US$6,000 per patient per year. 11 In order to know which therapy is appropriate for ESRD patients and to obtain positive outcomes, they have to consult a doctor, preferably a nephrologist because the decision depends on patient's choice, medical, social, and geographical considerations.…”
Section: Introductionmentioning
confidence: 99%